A q-switched thulium-doped fiber laser with a graphene thin film based saturable absorber - Saidin, N; Zen, D I M; Hamida, Belal Ahmed; Khan, Sheroz; Ahmad, Harith; Dimyati, Kaharudin; Harun, Sulaiman Wadi (IOP Publishing Ltd, 2013)
We demonstrate a simple, compact and low cost Q-switched thulium-doped fiber laser (TDFL) operating at 1844.1 nm by exploiting a graphene based saturable absorber (SA) in conjunction with 1552 nm pumping. The SA is fabricated by sandwiching the graphene thin film between two fiber connectors. The thin film was produced by mixing graphene flakes, synthesized by an electrochemical exfoliation process, with polyethylene oxide (PEO) solution. The TDFL generates a stable pulse train with 6.73 kHz repetition rate, 11.41 µs pulse width and 90.64 nJ pulse energy at 513 mW 1552 nm pump power. A higher performance Q-switched TDFL is expected to be achieved with the optimization of the SA and laser cavity.